The Physiological Significance of A-Waves in Early Diabetic Neuropathy: Assessment of Motor Nerve Fibers by Neurophysiological Techniques - Cai, Qiong; Aimair, Guliqiemu; Xu, Wen-Xiao; Xiao, Pei-Yao; Liu, Lie-Hua; Liang, Yin-Xing; Wu, Chao; Liao, Song-Jie (Frontiers in Systems Neuroscience, 2021)
Objective: This study aimed to investigate how early A-waves could occur in type II diabetes, and what it implied functionally. Methods: We performed conduction velocity distribution (CVD) test in peroneal nerves of 37 type II diabetic patients with normal nerve conduction study (NCS) and 22 age-matched controls. The electrophysiological data and clinical information were analyzed. Results: A-waves were observed in 45.9% of diabetic patients and only in 1 person in healthy controls, all detected in the tibial nerves. The diabetic patients with A-waves showed faster conduction velocity in all quartiles in the motor peroneal nerves compared to the patients without A-waves, and their CVD histograms were shifted to the right side, consisting of a significantly larger percentage of fast conducting fibers. There was no significant difference in the CVD values of the upper extremity nerves among the patients with and without A-waves and the healthy controls. Conclusion: A-waves could occur in type II diabetes as early as when NCS showed normal, and represented as a sign of neuropathy as well as a sign of rescued motor nerve function.